Incursions of the Brazilian Book: Ribeiro Couto and the Literary Diplomacy with Portugal and Cape Verde - Almeida Pinto, Bruna Carolina de [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2018)
The epistolary dialogue of Ribeiro Couto with Brazilian, Portuguese and Cape Verdean intellectuals reveals the atmosphere of an important moment in the history of intellectual and literary relations of the Portuguese language. This dialogue was recorded between the 1920s, when Ribeiro Couto began to live in Portugal, and 1963, the year of his death. As a member of the Brazilian Modernist Movement, Couto was productive and in the front line of the international dissemination of new nationalist writings produced in Brazil since the 1920s. The author faced it as a personal mission and a complementary project in the process of modernist autonomization. The purpose of this article is to indentify how Couto, using his diplomatic position in the international arena, sought to foster dialogues, partnerships and reflections. Moreover, his initiative even contributed to gather collaborators for the task of both introducing and projecting new Brazilian writers and their works into other cultural contexts.
Keywords: Brazilian literature; epistolography; intelectual history; modernism